2004
DOI: 10.2535/ofaj.80.127
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mono(2-ethylhexyl) Phthalate (MEHP) on Testes in Rats In Vitro

Abstract: Summary: The phthalate esters have been used as plasticizers for various plastic products, and their testicular toxicity has been reported. In this study, the effects of mono(2-ethylhexyl) phthalate (MEHP), one of the phthalate esters, on prepubertal rat testes in vitro were examined. The testes of 20-day-old Sprague Dawley (SD) rats were cut into smaller pieces and seeded in medium, and then the specimens were obtained for light and transmission electron microscopic observations. As a result, at 1 hr after ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…This prompted us to focus our attention to the primary effects of MEHP on Sertoli cells. Because determining a suitable MEHP concentration to use in the in vitro system and finding a logical correlation with the in vivo system were difficult, we concluded to use a 1 nmol/ml MEHP (low-dose) and 100 nmol/ml MEHP (high-dose) concentration based on findings from other researchers (Andriana et al 2004a, 2004b), who found significant damage to the Sertoli cells of rats and goats after MEHP exposure in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…This prompted us to focus our attention to the primary effects of MEHP on Sertoli cells. Because determining a suitable MEHP concentration to use in the in vitro system and finding a logical correlation with the in vivo system were difficult, we concluded to use a 1 nmol/ml MEHP (low-dose) and 100 nmol/ml MEHP (high-dose) concentration based on findings from other researchers (Andriana et al 2004a, 2004b), who found significant damage to the Sertoli cells of rats and goats after MEHP exposure in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of testicular function is caused by various mechanisms such as antiandrogenic effects of phthalate esters in rats [10] and fish [11], disruption of microtubule dynamics by Sertoli cell toxicants [12][13][14][15][16], disruption of Ca 2+ homeostasis [17], disruption of the blood-testis barrier via the mitogen-activated protein kinase signaling pathway The affected genes were classified into 12 functional categories according to "Gene Ontology".…”
Section: Discussionmentioning
confidence: 99%
“…The present study demonstrated the disruption of all stages of spermatogenesis predicted by histopathological alterations in 3-month-old transgenic rats. These disorders were marked in terms of seminiferous epithelial sloughing, vacuolization and degeneration in spermatocytes in addition to abnormal elongated spermatids and spermatozoa in the seminiferous lumen.cDNA microarray and realtime PCR analyses revealed that the expression levels of four genes (cnot7, fgf7, testin and ostf1) significantly increased (P<0.05) and that those of two genes (versican and mamdc1) decreased (P<0.05).Loss of testicular function is caused by various mechanisms such as antiandrogenic effects of phthalate esters in rats [10] and fish [11], disruption of microtubule dynamics by Sertoli cell toxicants [12][13][14][15][16], disruption of Ca 2+ homeostasis [17], disruption of the blood-testis barrier via the mitogen-activated protein kinase signaling pathway In the epididymides of the transgenic rat, degenerating round spermatids (B1) and many types of abnormal elongated spermatids (B2-4) were frequently observed. Abnormal spermatozoa showing a breakage of surface membranes (B5) and decline in the member of outer dense fiber were also observed (B-6).…”
mentioning
confidence: 99%
“…All these chemicals were obtained from Fluka AG, Bucha, SG. Polymerization was accomplished in oven at 60 Cº for 48 hours [4].…”
Section: -Electron Microscopymentioning
confidence: 99%